Incidence and Risk Factors of Preoperative and Postoperative Falls for Patients with Chronic Foot Pathologies: An Institutional Prospective Study. Issue 4 (22nd October 2020) - Alexander, Bradley; Cage, Benjamin B.; Greco, Elise M.; Sutherland, Charles R.; Halstrom, Jared R.; Solar, Spaulding F.; Sinha, Tanvee; Shah, Ashish; Andrews, Nicholas
Category: Other; Hindfoot; Lesser Toes; Midfoot/Forefoot Introduction/Purpose: Individuals with chronic foot pathologies often have an increased fall risk due to decreased power, deformity, or neuropathy. If patients do fall they can suffer injuries leading to emergency room visits, hospital admission, and surgery. Additionally, falls can increase the severity of their existing condition. This leads to an increase cost burden on the healthcare field and can ultimately decrease the quality of life for the patient. It is important to identify which foot pathologies are associated with the highest fall risk preoperatively and postoperatively. This study analyzes preoperative and postoperative fall data for patients with a variety of common forefoot, midfoot, and hindfoot pathologies. Methods: Over the course of 2019 70 patients had preoperative and 2-week and 6-week postoperative fall data collected in clinic prior to and after surgery. These patients were subdivided into three cohorts based on the location of foot pathology. This included 25 patients for forefoot, 20 patients for midfoot and 20 patients for hindfoot. We had patients complete several surveys that pertained to previous fall history, fall risks, fall history after surgery, current medical status, and use of an assistant device. The John's Hopkins Fall Risk Assessment tool and the survey pertaining to fall risk from the national council on aging were validated surveys that were completed. Results: Patients that suffered from a hindfoot pathology had the highest risk of suffering a fall preoperatively. Of the 25 patients in the hindfoot cohort 36% experienced at least one fall in the 12 months prior to surgery. Patients with forefoot and hindfoot pathologies experienced the most falls prior to surgery (0.64 and 0.60 respectively). Postoperatively patients with midfoot pathologies had the highest frequency of falls with 35% experiencing at least one fall within the 2-week period after surgery. The midfoot cohort also experience the most falls postoperatively averaging 0.50 falls. Preoperatively all patients completed a John's Hopkins fall risk assessment and the scores for forefoot midfoot and hindfoot were 6.32, 4.70, 6.96 respectively. With a score of over 6 indicating moderate fall risk. Conclusion: This information can help to identify which patients undergoing surgery for chronic foot pathologies are at the highest risk for preoperative and postoperative falls. Our study suggests that individuals with hindfoot pathologies are at greatest risk for preoperative falls and patients with midfoot pathologies have the greatest risk for postoperative falls. This study can help to guide patient management and decrease fall risk by understanding which patients are most susceptible. We are currently undertaking a prospective study looking at how preoperative mobility device training can reduce postoperative fall risk.